A prenatal acoustic signal of heat reduces a biomarker of chronic stress at adulthood across seasons - Udino, Eve; Oscos-Snowball, Marja A.; Buchanan, Katherine L.; Mariette, Mylene M. (Frontiers in Physiology, 2024)
During development, phenotype can be adaptively modulated by environmental conditions, sometimes in the long-term. However, with weather variability increasing under climate change, the potential for maladaptive long-term responses to environmental variations may increase. In the arid-adapted zebra finch, parents emit "heat-calls" when experiencing heat during incubation, which adaptively affects offspring growth in the heat, and adult heat tolerance. This suggests that heat-call exposure may adjust individual phenotype to hot conditions, potentially compromising individual sensitivity to cool weather conditions. To test this hypothesis, we manipulated individual prenatal acoustic and postnatal thermal experiences during development, and sought to assess subsequent chronic responses to thermal fluctuations at adulthood. We thus measured heterophil to lymphocyte (H/L) ratios in adults, when held in outdoor aviaries during two summers and two winters. We found that birds exposed to heatcalls as embryos, had consistently lower H/L ratios than controls at adulthood, indicative of lower chronic stress, irrespective of the season. Nonetheless, in all birds, the H/L ratio did vary with shortterm weather fluctuations (2, 5 or 7 days), increasing at more extreme (low and high) air temperatures. In addition, the H/L ratio was higher in males than females. Overall, while H/L ratio may reflect how individuals were being impacted by temperature, heat-call exposed individuals did not show a stronger chronic response in winter, and instead appeared more resilient to thermal variability than control individuals. Our findings therefore suggest that heat-call exposure did not compromise individual sensitivity to low temperatures at adulthood. Our study also reveals that prenatal sound can lead to long-term differences in individual physiology or quality/condition, as reflected by H/L ratios, which are consistent with previously-demonstrated reproductive fitness differences.